Key Habitat and Predatory Influences on the Community- and Species-Level Population Dynamics of Spring-Breeding Amphibian Larvae Within a Remnant Tupelo-Cypress Wetland - Jacob M. Hutton; Robin W. Warne (Hydrobiology)
Understanding the factors influencing amphibian populations is essential for effective freshwater conservation, particularly for species with biphasic life histories. This study examined how pond- and landscape-level characteristics shape larval amphibian occupancy, abundance, and detection in a remnant Tupelo-Cypress wetland in southeastern Illinois. Given the small number of available ponds (n = 4), we standardized survey effort across sites and incorporated robust hierarchical Bayesian models to evaluate environmental effects at both community and species levels. Occupancy probabilities were generally high across species, with canopy cover significantly increasing both community and species occupancy, particularly for salamanders (up to 6.4-fold). Predatory backswimmers and fish substantially reduced occupancy (by 21.7-fold and 6.0-fold, respectively). Anurans, especially Pseudacris spp., were more abundant than salamanders, with abundance positively associated with canopy cover, leaf litter, and pond perimeter. Detection probabilities were generally low and varied by species, with predatory invertebrates reducing detection up to 83.3-fold. These findings underscore the importance of maintaining canopy cover while mitigating predation risks to support amphibian populations. The application of multi-species hierarchical models provides a nuanced understanding of species-specific responses, offering valuable insights for conservation strategies in regions affected by habitat loss and climate change. However, given the limited spatial replication, these findings should be interpreted cautiously and validated through additional studies across broader temporal and spatial scales.